Management of Digit Papillomas in Golden Retriever Dogs - Jessica Anggun Safitri; Sarwo Edy Wibowo; Ahmad Syarifuddin; Dedi Damhuri; Puti Puspa Seruni; Asri Rizky (Journal of Applied Veterinary Science And Technology, 2025)
Background: Papillomas are benign tumors that affect the skin or soft tissue beneath the skin. These papillomas can be accompanied by various abnormalities such as pustules, itching, hematomas, cysts, blisters, abscesses, lick granulomas, and skintags. While papillomas may resolve on their own, some cases require intensive treatment and management. Purpose: To provide veterinarians with insights into diagnosing and managing papilloma cases. Case: A 10-year-old male Golden Retriever presented with an open wound on the left front paw nail. The wound originated from a broken nail, which led to a non-healing wound over a period of 2 months. Clinical examination revealed a mass-like lesion that had ruptured. Palpation of the left front paw nail area indicated an irregular, lobular growth resembling grapes or cauliflower. Case Management:  Routine hematology revealed that the dog had microcytic hypochromic anemia, while blood chemistry indicated mildly reduced kidney function. Cytology confirmed that the wound was a papilloma. Treatment involved digit amputation to completely remove the tumor mass, along with wound care that included the application of ointments, antibiotics, analgesics, hematopoietic agents, anti-bleeding medication, and anti-cancer drugs. Supportive treatment included multivitamins, nerve supplements, immune supplements, and skin and coat supplements (Coatex). By the fifth postoperative day, the wound had dried, and the edges were healing well. Conclusion: Papillomas are benign and not harmful, but it is recommended to completely remove the tumor mass to prevent secondary infections.